2020
DOI: 10.14710/jpki.15.2.59-64
|View full text |Cite
|
Sign up to set email alerts
|

Potret Self-system Remaja dengan Perilaku Tindakan Seksual Berisiko di Provinsi Jambi

Abstract: Background: Indonesia's largest population group is adolescents. Adolescents have a critical period in the human life cycle and put adolescents vulnerable to the influence of sexual risky behavior. The purpose of this study was to describe the self-portrait system that causes the sexual risky behavior of adolescents in Jambi Province.Method: This was quantitative research using a cross-sectional design. As much as 661 unmarried male and female adolescents (15-24 years) in Jambi Province involved as the sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Penelitian menunjukkan bahwa remaja yang aktif melakukan hubungan seksual memiliki risiko lebih tinggi untuk terkena penyakit menular seksual (PMS) dan kehamilan yang tidak diinginkan (Askhori, 2021;Sulastri & Astuti, 2020;Sunardi et al, 2020). Selain itu, kehamilan di luar nikah dapat menimbulkan stigma sosial dan ekonomi yang dapat mempengaruhi masa depan remaja.…”
Section: )unclassified
“…Penelitian menunjukkan bahwa remaja yang aktif melakukan hubungan seksual memiliki risiko lebih tinggi untuk terkena penyakit menular seksual (PMS) dan kehamilan yang tidak diinginkan (Askhori, 2021;Sulastri & Astuti, 2020;Sunardi et al, 2020). Selain itu, kehamilan di luar nikah dapat menimbulkan stigma sosial dan ekonomi yang dapat mempengaruhi masa depan remaja.…”
Section: )unclassified
“…When the decisions made in dealing with conflict were not right, most of them fall into negative behaviours, and have to bear the short and long-term consequences of various physical and psychosocial health problems, such as adverse events and other medical effects. 9,30 The increase of knowledge by providing exposure information, needs to be provided according to their age. This should be carried out through the use of promotional media, which are light, informative, and educative.…”
Section: Many Factors Influenced the Occurrence Of Up Inmentioning
confidence: 99%
“…1 Moreover, results of the previous study stated that women with UP do not provide exclusive breastfeeding and complete basic immunization, as pregnancy care was also not carried out according to the criteria. 3,9 Also, UP is caused by unhealthy behaviours and conditions at the time before or during pregnancy, such as rape, lack of knowledge about contraception, too many children, health reasons, fetal defects, young age, irresponsible spouses, and unstable relationship with partners. This is closely related to the sociodemographic conditions of the family (low income), culture, and societal beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…Risky adolescent sexual behavior can be caused by 2 factors, namely; internal factors and external factors. Based on several studies, it was found that factors can influence the incidence of untimely pregnancy in adolescents, namely knowledge, attitudes and actions [24] ( [24]; Ayele et al, 2018; Jannah, 2018; Fitrian et al, 2019;Sunardi et al, 2020) and external factors are permissive parenting patterns, peer pressure, use of technology and religiosity [25].…”
Section: Introductionmentioning
confidence: 99%
“…The 2017 Indonesian Demographic and Health Survey highlights that adolescent girls and boys who have/are currently dating have risky behavior. This is proven by the fact that 28% of female teenagers stated that they had been exposed to several forms of risky sexual behavior, such as hugging, kissing, touching and touching sexual organs [30].…”
Section: Introductionmentioning
confidence: 99%